Synaptic Mitochondria: An Early Target of Amyloid-β and Tau in Alzheimer's Disease - Torres, Angie K.; Jara, Claudia; Park-Kang, Han S.; Polanco, Catalina M.; Tapia, Diego; Alarcon, Fabian; de la Pena, Adely; Llanquinao, Jesus; Vargas-Mardones, Gabriela; Indo, Javiera A.; Inestrosa, Nibaldo C.; Tapia-Rojas, Cheril (My University, 2021)
Alzheimer's disease (AD) is characterized by cognitive impairment and the presence of neurofibrillary tangles and senile plaques in the brain. Neurofibrillary tangles are composed of hyperphosphorylated tau, while senile plaques are formed by amyloid-beta (A beta) peptide. The amyloid hypothesis proposes that A beta accumulation is primarily responsible for the neurotoxicity in AD. Multiple A beta-mediated toxicity mechanisms have been proposed including mitochondrial dysfunction. However, it is unclear if it precedes A beta accumulation or if is a consequence of it. A beta promotes mitochondrial failure. However, amyloid beta precursor protein (A beta PP) could be cleaved in the mitochondria producing A beta peptide. Mitochondrial-produced A beta could interact with newly formed ones or with A beta that enter the mitochondria, which may induce its oligomerization and contribute to further mitochondrial alterations, resulting in a vicious cycle. Another explanation for AD is the tau hypothesis, in which modified tau trigger toxic effects in neurons. Tau induces mitochondrial dysfunction by indirect and apparently by direct mechanisms. In neurons mitochondria are classified as non-synaptic or synaptic according to their localization, where synaptic mitochondrial function is fundamental supporting neurotransmission and hippocampal memory formation. Here, we focus on synaptic mitochondria as a primary target for A beta toxicity and/or formation, generating toxicity at the synapse and contributing to synaptic and memory impairment in AD. We also hypothesize that phospho-tau accumulates in mitochondria and triggers dysfunction. Finally, we discuss that synaptic mitochondrial dysfunction occur in aging and correlates with age-related memory loss. Therefore, synaptic mitochondrial dysfunction could be a predisposing factor for AD or an early marker of its onset.
Keywords: alzheimer's disease; amyloid-beta; amyloid-beta protein precursor; cognitive impairment; mitochondria; neurofibrillary tangles; synapses; synaptic mitochondria